Implementation of Learning Media Using Augmented Reality Technology for Senior High School Students - Rosynanda Nur Fauziah; Dwi Sulisworo (Jurnal Pembelajaran Fisika, 2021)
This study was to determine the use of learning media using augmented reality technology which is applied to senior high school students. The research method used in this research is quasi-experimental with the research design using treatment before and after the use of the learning media. Quasiexperimental as an experiment that has treatment, impact measurement, experimental unit, but does not use random assignment to create comparisons in order to conclude changes caused by treatment. The results of the research conducted for the results of the pre-test or before the students received treatment were 69,2%, while the results of the post-test or after the students received treatment were 91%. Then for the average value of the combination of the two tests can be said to be good with the use of learning media using Augmented Reality technology, which is 80,1%. From these results it can be concluded that the application of learning media using Augmented Reality technology provides changes to student learning outcomes in terms of understanding the concept of physics, thus the application of learning media with Augmented Reality technology is successfully applied to high school students for physics subjects.Keywords: augmented reality, learning media, technologyDOI:http://dx.doi.org/10.23960/jpf.v9.n2.202109